2012
DOI: 10.1007/s11999-012-2452-y
|View full text |Cite
|
Sign up to set email alerts
|

Slipped Capital Femoral Epiphysis: Prevalence, Pathogenesis, and Natural History

Abstract: Background Obesity is a risk factor for developing slipped capital femoral epiphysis (SCFE). The long-term outcome after SCFE treatment depends on the severity of residual hip deformity and the occurrence of complications, mainly avascular necrosis (AVN). Femoroacetabular impingement (FAI) is associated with SCFE-related deformity and dysfunction in both short and long term. Questions/Purposes We examined obesity prevention, early diagnosis, reducing AVN and hip deformity as strategies to reduce SCFE prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 71 publications
1
91
0
15
Order By: Relevance
“…Contemporary goals of surgical treatment of severe SCFE beyond stabilization of the physis include realignment of the proximal femur to restore the femoral head-neck anatomy and allow for better arc of hip motion, thereby avoiding FAI [27,28]. Corrective osteotomies performed at the subcapital level have the advantage of complete restoration of the femoral anatomy but are associated with potential risk of osteonecrosis of the femoral head [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary goals of surgical treatment of severe SCFE beyond stabilization of the physis include realignment of the proximal femur to restore the femoral head-neck anatomy and allow for better arc of hip motion, thereby avoiding FAI [27,28]. Corrective osteotomies performed at the subcapital level have the advantage of complete restoration of the femoral anatomy but are associated with potential risk of osteonecrosis of the femoral head [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Excess weight places stress on the joints and quickly wears down the cartilage. Numerous studies have reported that CD is more severe and occurs more frequently in obese adult female populations compared to ageand gender-matched (female) normal weight groups (24)(25)(26). Felson (27) found that age-matched elderly obese women had greater progression of knee OA compared to women of a normal weight, which was proposed to be due to abnormal mechanical stress of the knee joint.…”
Section: Discussionmentioning
confidence: 99%
“…Hip X-rays help in diagnosis. If the X-ray is suggestive of SCFE, an immediate orthopedic consult should be sought 24 ( Figure 5). …”
Section: Othermentioning
confidence: 99%